Using the spectrum of dark radiation as a probe of reheating - Jaeckel, Joerg; Yin, Wen (Physical review, 2021)
After inflation the Universe presumably undergoes a phase of reheating which in effect starts the thermal big bang cosmology. However, so far we have very little direct experimental or observational evidence of this important phase of the Universe. In this paper, we argue that measuring the spectrum of freely propagating relativistic particles, i.e., dark radiation, produced during reheating may provide us with powerful information on the reheating phase. To demonstrate this possibility we consider a situation where the dark radiation is produced in the decays of heavy, nonrelativistic particles. We show that the spectrum crucially depends on whether the heavy particle once dominated the Universe or not. Characteristic features caused by the dependence on the number of the relativistic degrees of freedom may even allow to infer the temperature when the decay of the heavy particle occurred.
Gesehen am 05.08.2021